Analisis Proses Komunikasi Pemerintah Nagari Dalam Menyampaikan Informasi Kepada Masyarakat Di Nagari Alahan Nan Tigo, Dharmasraya - Yesi Sumarni; Dion Eriend (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The Nagari government communication process is a rule that is conveyed regarding the stages of conveying information to the public. Information is a collection of data or messages that have been processed to obtain knowledge that is more useful for achieving a goal. The target of an information about the village of Alahan Nan Tigo is the Nagari community. In the process of conveying information, those who are responsible for conveying information are the nagari secretary and the jorong head who are conveyed directly by gathering the community in one place and through the media such as being contacted by telephone. besides that the communication process in conveying information also utilizes social media Facebook and Instagram nagari which are managed by the nagari treasurer. The research method used in this study is qualitative with a descriptive approach and uses Joseph Devito's theory. The results of this study are that the communication process in conveying information is carried out in stages which will be directly coordinated by the nagari secretary to the jorong head who is then responsible for conveying information to the community, this coordination is carried out directly at the wali nagari office and also through the nagari government group. In addition, in conveying information, social media is also used, namely Facebook and Instagram Nagari.